Biology and epidemiology of Diaporthe amygdali: understanding how environmental factors influence fungal growth, sporulation, infection and lesion development on almond - Francia, Carolina; Lázaro, Elena; Novellón, Maite; Ramón-Albalat, Antonio; Beluzán, Francisco; Vicent, Antonio; Berbegal, Mónica; Armengol, Josep (Frontiers in Plant Science, 2025)
IntroductionDiaporthe amygdali is a major pathogen causing twig canker and shoot blight disease on almond crops. Knowledge about the influence of environmental factors on the biology and epidemiology of this pathogen has mainly been obtained on peach, but there is scarce information on almond. Thus, the main objective of this research was to better understand how environmental factors, such as temperature and wetness periods, determine the cycle of this disease on almond crops in Mediterranean conditions.MethodsSeveral experiments were conducted to obtain information about mycelial growth, sporulation, plant infection and lesion development using almond isolates of D. amygdali.ResultsOur results showed that the temperature ranges for both α-conidia germination and almond infection are broad and overlap (between 5 and 35°C), potentially allowing infections to occur year-round. Nevertheless, the highest infection of almond plants was observed after 72 h of wetness period, while the lowest occurred after 6 h, explaining why D. amygdali is a prevalent disease in spring and autumn when rain events are more frequent.DiscussionMycelial growth of D. amygdali and lesion development were promoted by warm temperatures. The production of mature pycnidia on cankers had lower and narrower temperature requirements, thus suggesting an adaptation to late winter and early spring conditions. Moreover, the optimum temperature for α-conidia production in pycnidia was around 22°C. All this information could be used to develop a mechanistic model for almond twig canker and shoot blight disease management to enhance the timeliness and effectiveness of control strategies, while reducing both economic costs and environmental impacts.